Fisioterapi Dan Yoga Dalam Mengatasi Nyeri Pinggang Kronis - Yuliari, Sang Ayu Made; Cahyaningrum, Putu Lakustini; Putra Suta, Ida Bagus (Jayapangus Press, 2025)
Healthy is the dream of every person living on this earth. However, in the course of life, humans experience pain, such as low back pain experienced by people aged 50 years and over. To overcome this, the therapist uses two methods, namely physiotherapy and yoga exercise. Based on this, this research aims to find out more about physiotherapy and yoga in treating chronic low back pain, its procedures and implications. To achieve this goal, qualitative data is uses with purposive sampling tecniques, data collection through observation,in-depth interviews, documentation, literature studies and health theory and structural functionalism.Based on these methods and theories, the results obtained are, 1) Physiotherapy and Yoga can overcome low back pain more quickly because they complement each orther and have the function of improving blood circulation,treating pain, relaxing, increasing muscle elasticity and flexibility, managing emotions and increasing lactic acid. 2) Physiotherapy procedures, namely, start by asking the patient about the complaint they are feeling, after that it is treated with modalities according to the complaint such as infrared, ultrasound and Tens as well as yoga procedures in the form of asanas such as Cobra /bhujanggasana, Cat/Marjariasana, flappingfish/Matsya kridasana and bridge/setubandha. 3) Based on data from 30 patients with 16 men and 14 women, ther are two types of treatment, namely physiotherapy and physical exercise in the form of asanas. The results of the treatment show two patterns, namely (a) Patients who undergo 3 therapy sessions and 2 physicl exercise sessions ten to recover, (b) Patients hwo underwent 8 therapy sessions and 1 physical exercise experienced a reduction in paint, but were not completely cured. The implication of this therapy was that the patient felt happy, relaxed, warm and grateful so that endhorphins increased.